APPLYING THE GARDEN CITY CONCEPT TO HISTORIC GUANAJUATO (JÓVENES EN LA CIENCIA, 2018)
The rapid development of population centers has caused the problem of lack of green areas in urban contexts. As a contribution to the search for urban sustainability, planners are resuming and applying the concept of Garden City, developed by Ebenezer Howard at the end of the 19th century. Emphasizing the distribution and function of green spaces as a main component in the planning of land use, the original idea of Garden City seeks to provide a safe, environmentally healthy and comfortable place for urban residents that allows interaction between them. Similarly, when considering sufficient open space, an easily legible land use distribution is sought, with an integrated road and transport system that connects residential areas with other land uses in the urban context. Some of Howard's ideas were put into practice, for example, in the cities of Letchworth and Welwyn, located near London, in England from 1968. However, the concept itself becomes more defined and clear until the 1980s. This research project will analyze the feasibility of implementing the concept of Garden City in Guanajuato, Gto., Mexico.
Keywords: Array; Array; Array